Spatiotemporal glacier retreat on the Tibetan Plateau since the LGMG to early holocene based on compilation of moraine boulder ages - Chaogang Zheng; Zhigang Zhang; Xinggong Kong; Darryl Granger; Zhijun Zhao; Z. Zhang (Scientific Reports)
Abstract Tibetan Plateau and its surrounding mountains (TPSM) have experienced prominent glacier retreat since the Global Last Glacial Maximum, while the detailed deglaciation process remains unclear. To investigate the spatiotemporal pattern of the glacier retreat history, we compiled 196 moraines dating from 26.5 to 10 ka based on 994 boulder 10Be exposure age from seven regions on the TPSM and calculated the separated component Gaussians of moraine ages. The result shows that synchronous glacier retreat across the entire TPSM began around 22 ka in response to onset of rising local summer insolation. Moraine abandonment centered at five stages, i.e., 22–20, 19–18 ka, 17–16, 14.5–12.9, and 11.6–10 ka. Synchronous retreat occurred at 22–20 ka and 14.5–12.9 ka in all seven regions, while at 19–18 ka, it occurred in all regions except Tianshan. Pamir and NE Tibet showed no retreat at 17–16 ka, likely due to the sustained influence of the Westerlies. The stage at 11.6–10 ka was absent in Central Tibet due to lack of chronology from the perched moraines therein. This work offers new insights into the evolution of the cryosphere and adjustments in atmospheric circulation on the TPSM.